Tricky with Heat and Salt: Soil Factors, Thermotaxis, and Potential for Heat–Saline Agar Trapping of Strongyloides Larvae - Nuttapon Ekobol; Sirintip Boonjaraspinyo; Chatanun Eamudomkarn; Thidarut Boonmars (Biology)
The viability and host-seeking behavior of Strongyloides larvae are significantly influenced by soil conditions, emphasizing the critical role of environmental control in disease management. This is particularly relevant given the growing concerns about drug resistance resulting from mass chemotherapy or the use of chemical nematicides. Strongyloides stercoralis was effectively inactivated by exposure to 50 °C for both 12 and 24 h (long-term exposure). Strongyloides ratti was inactivated by 50 °C for 20 min (short-term exposure), 9% saline for 50 min, and a combination of 4% saline and 40 °C for 50 min. The combined treatment successfully inactivated S. ratti in four soil mediums using 5% saline at a central temperature of 40 °C. Thermotaxis responses to noxious heat revealed attraction at 40 °C, increased localized searching at 45 °C, and complete inactivation at 50 °C. Larvae migrating within agar at 45 °C were more readily inactivated. Long-range heat attraction at 5 cm resulted in the inactivation of up to 50% of incoming larvae; however, heat-high concentration saline traps at 3 cm distance proved ineffective. Thermal–saline agar trapping demonstrated promise for larval removal in sand, loam, and laterite soils. This method offers a promising approach to larval removal while minimizing hazards to non-target organisms.